La neurodidáctica en el fortalecimiento del rendimiento académico a través de un sistema de actividades didácticas de los estudiantes del centro de desarrollo infantil tía Nelly del Cantón La Maná - Lagos Vélez, Gisela Monserrate (2021)
The present research entitled "Neurodidactics in the strengthening of academic performance through a system of actions of the students of the Child Development Center (CDI) Tía Nelly del Cantón La Maná" has as its main objective to analyze the incidence of neurodidactics in the academic performance of the students of the CDI Tía Nelly del Cantón Maná through the application of a system of didactic activities. Neurodidactics is recognized as a way to promote new techniques of educational praxis, as part of the brain development, being this the one that allows to obtain a better learning seeing the qualities of the individual that are essential for their formation and dialogue, breaking traditional paradigms and innovating new tendencies in the didactic methodology that motivates the teacher to carry out new forms of learning, strengthening the knowledge that the student already possesses and offering him through brain stimulation the necessary tool for his continuous formation and learning. The research is based on the research-action methodology, from a mixed approach that in the diagnosis analyzes the result of the application of surveys made to the 8 teachers, in addition to the observation of the classes and the selection of a focal group. Its result serves as a basis for the design of a system of didactic activities based on neurodidactic foundations for the improvement of the academic performance of the students of the CDI Tía Nelly of Cantón Maná for the validation of the realization of the proposal within the expected results the research could observe how the teacher when using activities with neurodidactic foundations stimulates the participation of the child improving his academic performance, and how in turn through art, play, music and emotions he experiences new levels of learning.